Implementasi Pembelajaran Problem Based Learning (PBL) di SMP Ghautsul Ibaad Kelas IX dalam Membentuk Karakter Sosial Peserta Didik - Muhamad Rifqy Al Ghifari; Heri Kurnia (Academy of Social Science and Global Citizenship Journal, 2026)
Social character education at the junior high school level still faces challenges in developing a quality generation, characterized by apathy and intolerance among adolescents. The Problem-Based Learning (PBL) model offers a real-world problem-based approach that encourages critical thinking skills, collaboration, and the development of social character traits such as cooperation, empathy, and responsibility in ninth-grade students at SMP Ghautsul Ibaad, a boarding school. This study analyzes the implementation of the Problem-Based Learning (PBL) model at SMP Ghautsul Ibaad to shape students' social character and address challenges in character education in Indonesia, such as intolerance and a lack of social awareness that are still prevalent. PBL encourages students to solve real-world problems collaboratively, improving critical thinking skills, cooperation, empathy, communication, and discipline, based on previous studies. The main objective is to describe the effective implementation of PBL and recommend this method as an active learning solution that builds a generation with positive character, despite the challenges it faces. The method used in this study is descriptive qualitative, with data collection techniques including observation, interviews, and documentation of the learning process. The results of the study indicate that the implementation of PBL in ninth-grade students at Ghautsul Ibaad Middle School encouraged students to be more active in group discussions, respect others' opinions, and develop a habit of making decisions together. Furthermore, students were more involved in social activities that required cooperation and mutual assistance. In conclusion, PBL implementation is effective in shaping students' social character because it positions them as the subjects of learning, accustoms them to positive interactions, and instills the values of cooperation and empathy through problem-solving relevant to their social environment.